Influence of a Concentrated Ethylester Compound of n-3 Fatty Acids on Lipids, Platelets and Coagulation in Patients Undergoing Coronary Bypass Surgery - Nilsen, D W T; Dalaker, K; Nordøy, A; Østerud, B; Ingebretsen, O C; Lyngmo, V; Almdahl, S; Vaage, J; Rasmussen, K (Thrombosis and Haemostasis, 1991)
Twenty patients accepted for coronary bypass surgery were randomized to receive either a concentrated ethylester compound of n-3 fatty acids, with a daily dose of 3.15 g of eicosapentaenoic acid (EPA) and 1.89 g of docosahexaenoic acid (DHA), or corn oil (controls) in a double blind study, to evaluate the effect on lipids, platelets and coagulation during the pre- and postoperative phase.Only patients with fasting triglyceride (TG) levels ≥1.6 mmol/1 at recruitment were eligible. The study was continued for 5 to 6 months. Surgery was usually performed at mid-intervention. Blood samples were collected during morning hours in fasting subjects, just prior to intervention, preoperatively and at final postoperative follow-up. Moreover, blood loss was accurately accounted for postoperatively.A threefold increase (p = 0.0001) of EPA was noted at pre-and postoperative follow-up. TG-levels were reduced 20 and 39%, respectively, in patients on n-3 fatty acids, reaching statistical significance at end of intervention (p = 0.034). TG-levels in controls remained largely unchanged. In patients on n-3 fatty acids, there was a statistically significant increase in serum total cholesterol preoperatively, but this change was no longer present at completion of the study.No significant changes were noted in platelet function, as judged by bleeding time, collagen induced platelet aggregation and release of TxB2 during aggregation. Parameters of extrinsic coagulation, including phospholipase C-sensitive factor VII (PLC-VII) and extrinsic pathway inhibitor (EPI), also remained essentially unchanged in both groups of patients. However, fibrinogen was significantly reduced in controls (p <0.05) at end of intervention. Moreover, a strong positive correlation was noted between PLC-VII and TG (r = 0.77, p = 0.0001).No significant difference in postoperative bleeding was noted between the two groups of patients.